THE EFFECTIVENESS OF PEER REVIEW TO TEACH WRITING VIEWED FROM STUDENTS’ MOTIVATION AT NINTH GRADE OF SMP N 1 SEKAMPUNG ACADEMIC YEAR 2014/2015 - Leny Setiyana (Jurnal Pedagogy, 2016)
This research is aimed to examine whether ;(1) Peer Review is more effective than Think Pair Share Technique to teach writing for the ninth grade students; (2) The students with high motivation have better writing skill than those having low motivation for the ninth grade students; and (3) There is an interaction between teaching techniques and students’ motivation in teaching writing for the ninth grade students. The method that was used in this research is experimental study. The samples were two classes namely experimental class which was taught using Peer Review and control class which was taught using Think Pair Share. Each class was divided into two groups of which each consisted of students having high motivation and those having low motivation. Two instruments were used to collect the data. The instruments were writing test and motivation’s questionnaire. The data were analyzed by using Multifactor Analysis of Variance ANOVA 2x2 and Tukey Test. Before conducting ANOVA test, pre-requisite test was conducted. Based on the data analysis, the findings of this research are; (1) Peer Review technique is more effective than Think Pair Share technique to teach writing; (2) The students with high motivation have more better writing skill than those having low motivation; and (3) There is an interaction between teaching techniques and students’s motivation in teaching writing. The research result of this study implies that Peer Review technique is effective to teach writing for the ninth grade students.